DAMPAK APLIKASI YOUTUBE TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA DINI - Ziadatul Mardhiah; Hardiyanti Pratiwi; Rusdiah Rusdiah (JEA (Jurnal Edukasi AUD), 2022)
The YouTube application is one of the many social media that is often used by the public, both adults and children. The rise of YouTube applications for children is one of the problems in the world of education. Along with the increasingly rapid development of the times, of course this will have an impact on the development of children if parents continue to provide YouTube applications. This study aims to determine the impact of the YouTube application on children's cognitive development. This type of research is field research with a qualitative approach. The method used in this study is a qualitative descriptive method. The subjects in this study were six children aged 4-6 years and their parents (housewives). The object of research is the impact of the YouTube application on children's cognitive development. Data was collected through observation, interviews, and documentation. Data analysis uses Miles and Huberman analysis which is carried out interactively and takes place continuously. Based on the results of the study, it can be concluded that: the impact of the YouTube application on the cognitive development of the 6 children is, being able to recognize the letters of the alphabet, hijaiyah letters, recognizing colors, recognizing numbers and being able to count, being able to memorize, easy to imitate, learning through songs, recognizing large and small objects, and group images.